AI technology, technology and the future of humanity - Liu, Yiming (Transactions on Economics, Business and Management Research, 2024)
As an important part of modern technology, artificial intelligence (AI) technology has made remarkable progress in many fields and has had a profound impact on human society. This paper discusses the development status and trend of AI technology, the reasons and background of its rise, and its application and impact in today’s society. By analyzing the role of AI technology in promoting the progress of human civilization and scientific and technological progress, as well as its future development prospects and challenges, this paper aims to explore the important role of AI technology in promoting social progress and improving the quality of human life.